Peningkatan Keterampilan Berbicara Siswa Kelas X SMK Negeri 1 Bunga Mayang Kabupaten Oku Timur dalam Pembelajaran Daring (Online) Berbasis E Learning dengan Media Digital Storytelling - Kodri, Agus; Missriani, Missriani; Fitriani, Yessi (STKIP PGRI Bandar Lampung, 2023)
The research entitled improving the speaking skills of class X students at SMK Negeri 1 Bungan Mayang, east OKU regency in online learning (online) based on e learning with digital storytelling media which aims to describe the application of storytelling on aspects og speaking skills in each cycle of learning Indonesia for class X students of SMK Negeri 1 east OKU Bunga Mayang. This research is an action research to improve student learning outcomes and improve the learning process in the classroom. The results showed learning outcomes in terms of knowledge, ini increasing learning in each learning cycle there was an increase in students mastery and absorption, namely completeness in cycle I 70.58%, absorption capacity 52.35%, and cycle II 70.58%, completeness level 88.23%, and absorption rate of 76.76%. Similarly the skill aspect increased in the first cycle 76.47% completeness and 55.88% absorption. In the second cycle it increased again 88.23% completeness and 77.35% absorption. Then, learning outcomes increased during learning in class X TKJ SMK Negeri 1 Bunga Mayang OKU Timur, students speaking skills developed from cycle I to cycle II as well as skills in cycle I reached 76.47% and increased to 77.35%.